Development of a software to describe the temporal evolution of landforms. - Vaiopoulos, D.; Skianis, G.; Vassilopoulos, A.; Evelpidou, N. (COST 634 Conference ‘Soil and Hillslope Management using Scenario Analysis and Runoff-Erosion models: a Critical Evaluation of Current Techniques’, 2007)
In the present paper we develop a software in order to describe, in quantitative terms, the time variation of the shape and dimensions of a landform. The software is based on an iterative cellular automata algorithm. In each step, the algorithm calculates the altitude and soil thickness of each cell, which represents a piece of land. The calculations are based on the continuity equation. Parameters which express the intensity of weathering of rock masses, soil transport along slopes and fluvial transport of sediments by rivers (physical processes parameters), are incorporated in the continuity equation, using empirical relations. These parameters may be time constant or time dependent. The physical meaning of a time dependent parameter is that the rate of a geomorphological process may change with time, as a result of human activities or changes in the climate. The temporal variation of the physical processes parameters are expressed by simple mathematical expressions, which may represent smooth, rapid or periodical changes. This software may be useful in geomorphological and environmental research, in order to estimate the future development of a landform, as a result of physical processes and human activities.